Prevalence of Musculoskeletal Disorders among Dental Professionals: An Umbrella Review - Jain, Lisha; Hegde, Vivek; Shetty, Rajesh; Tandale, Anita; Palekar, Tushar J.; Mehta, Vini; S.R, Srinidhi; Negi, Sapna (European Journal of General Dentistry, 2024)
Performing repetitive tasks on patients' mouths increases the risk of strain-related injuries for dental professionals, ultimately leading to musculoskeletal disorders (MSDs). This umbrella review aims to assess the scope of the MSD problem and identify the most often impacted body parts among dental professionals. A comprehensive search of the literature was performed from inception to March 30, 2024, in PubMed-MEDLINE, Embase, Scopus, and Web of Science databases. This review evaluated systematic reviews (SRs) and meta-analyses (MAs) of the observational studies that reported the prevalence of MSDs or any form of MSD among dental professionals such as dentists, dental hygienists, or dentistry students. The extracted data were complemented with narrative synthesis. A total of eight SRs and MAs were included in this umbrella review. Five of the eight studies were conducted globally, one in the context of Western countries and two in an Iranian context. Four of the eight studies focused on MSDs in dental practitioners, with prevalence rates ranging from 0.5 to 93%. Four body areas, that is, the neck, the lower and upper back, the shoulders and wrists, and hands were widely exposed to MSDs, with significant prevalence reported across studies. In conclusion, MSDs are common among dental professionals. Consequently, there is a pressing need to implement infrastructural and behavioral ergonomic solutions in the dental profession. However, a major concern arises from the critically low quality of available studies on MSD prevalence in dental professionals. Therefore, more rigorous research adhering to the basic quality criteria is required.
Keywords: musculoskeletal diseases; dentists; ergonomics